2017
DOI: 10.1186/s13059-016-1137-3
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic signatures differentiate survival from fatal outcomes in humans infected with Ebola virus

Abstract: BackgroundIn 2014, Western Africa experienced an unanticipated explosion of Ebola virus infections. What distinguishes fatal from non-fatal outcomes remains largely unknown, yet is key to optimising personalised treatment strategies. We used transcriptome data for peripheral blood taken from infected and convalescent recovering patients to identify early stage host factors that are associated with acute illness and those that differentiate patient survival from fatality.ResultsThe data demonstrate that individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
187
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(200 citation statements)
references
References 48 publications
(64 reference statements)
12
187
0
1
Order By: Relevance
“…In addition to up‐regulation and hypersecretion of pro‐ and anti‐inflammatory chemokines and cytokines that were previous appreciated to occur, changes in expression of a large number of previously unappreciated genes were identified. Expression of some of these correlated with survival . Of note, many cytokines/chemokines, identified in previous studies to have altered expression during EBOV infection, were not identified in these studies; however, differences in approach as well as differences between transcriptional and translational changes may partially account for this.…”
Section: Ebov Elicits Mϕ Immunopathologymentioning
confidence: 72%
“…In addition to up‐regulation and hypersecretion of pro‐ and anti‐inflammatory chemokines and cytokines that were previous appreciated to occur, changes in expression of a large number of previously unappreciated genes were identified. Expression of some of these correlated with survival . Of note, many cytokines/chemokines, identified in previous studies to have altered expression during EBOV infection, were not identified in these studies; however, differences in approach as well as differences between transcriptional and translational changes may partially account for this.…”
Section: Ebov Elicits Mϕ Immunopathologymentioning
confidence: 72%
“…The ability of EBOV to impact the number of circulating lymphocytes has been extensively described in mice [4], in non human primates [3] and in humans [6]. A decrease in NK cells was shown in animal models [5] and recently suggested in humans by a molecular profiling approach [20]. Moreover, a specific early loss of both NK and γδ T-cells was described also in other acute hemorrhagic fever models [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…64 A transcriptomic analysis of blood RNA from EBOV-infected patients showed elevated expression levels of genes associated with interferons and acute phase signaling pathways. 65 Lower levels of inflammation correlated with virus clearance and robust EBOV-specific T-cell responses. Although these novel data provide insight into innate and adaptive immune responses, their contribution to protection in humans is still not defined.…”
Section: Correlates Of Protection and Duration Of Immune Responsesmentioning
confidence: 97%